2013
DOI: 10.1021/ja4029582
|View full text |Cite
|
Sign up to set email alerts
|

Nanomolar E-Selectin Antagonists with Prolonged Half-Lives by a Fragment-Based Approach

Abstract: Selectins, a family of C-type lectins, play a key role in inflammatory diseases (e.g., asthma and arthritis). However, the only millimolar affinity of sialyl Lewis(x) (sLe(x)), which is the common tetrasaccharide epitope of all physiological selectin ligands, has been a major obstacle to the development of selectin antagonists for therapeutic applications. In a fragment-based approach guided by NMR, ligands binding to a second site in close proximity to a sLe(x) mimic were identified. A library of antagonists … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 77 publications
0
44
0
1
Order By: Relevance
“…This increases the avidity of the low-affinity monovalent carbohydrate recognition (K d (mannose) = 3.5 mm [5] )i nto the nanomolar range for multivalent interactions (K d (gp120) = 1-2 nm [6] ). [10] However, such approaches capitalize on the presence of extended binding sites that allow for affinity maturation of the core scaffold by the attachment of hydrophobic substituents.S uch secondary sites are often neither well-described nor directly accessible from the analysis of crystallographic structures as they might stem from minor alterations of the protein geometry.P revious reports indicated the presence of binding sites for drug-like molecules to DC-SIGN, [9,11] and as these inhibitors lack functional groups to directly interact with the primary Ca 2+ ion, an allosteric mechanism was proposed. [8] In contrast, such noncarbohydrate,d rug-like DC-SIGN inhibitors are limited to quinoxalinones.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This increases the avidity of the low-affinity monovalent carbohydrate recognition (K d (mannose) = 3.5 mm [5] )i nto the nanomolar range for multivalent interactions (K d (gp120) = 1-2 nm [6] ). [10] However, such approaches capitalize on the presence of extended binding sites that allow for affinity maturation of the core scaffold by the attachment of hydrophobic substituents.S uch secondary sites are often neither well-described nor directly accessible from the analysis of crystallographic structures as they might stem from minor alterations of the protein geometry.P revious reports indicated the presence of binding sites for drug-like molecules to DC-SIGN, [9,11] and as these inhibitors lack functional groups to directly interact with the primary Ca 2+ ion, an allosteric mechanism was proposed. [8] In contrast, such noncarbohydrate,d rug-like DC-SIGN inhibitors are limited to quinoxalinones.…”
mentioning
confidence: 99%
“…[8] In contrast, such noncarbohydrate,d rug-like DC-SIGN inhibitors are limited to quinoxalinones. [10] However, such approaches capitalize on the presence of extended binding sites that allow for affinity maturation of the core scaffold by the attachment of hydrophobic substituents.S uch secondary sites are often neither well-described nor directly accessible from the analysis of crystallographic structures as they might stem from minor alterations of the protein geometry.P revious reports indicated the presence of binding sites for drug-like molecules to DC-SIGN, [9,11] and as these inhibitors lack functional groups to directly interact with the primary Ca 2+ ion, an allosteric mechanism was proposed. [10] However, such approaches capitalize on the presence of extended binding sites that allow for affinity maturation of the core scaffold by the attachment of hydrophobic substituents.S uch secondary sites are often neither well-described nor directly accessible from the analysis of crystallographic structures as they might stem from minor alterations of the protein geometry.P revious reports indicated the presence of binding sites for drug-like molecules to DC-SIGN, [9,11] and as these inhibitors lack functional groups to directly interact with the primary Ca 2+ ion, an allosteric mechanism was proposed.…”
mentioning
confidence: 99%
“…The specific E‐selectin inhibitor, GMI‐1271, is also being evaluated in the clinic in combination with chemotherapy to treat acute myeloid leukemia 78. Another example of selectin inhibitors comes from the Ernst laboratory, who used an NMR guided fragment‐based approach for the design and synthesis of a nanomolar E‐selectin antagonist derived from sLe x as a promising candidate in search of novel anti‐inflammatory drugs 79. Following a similar approach, the same research group identified high‐affinity sialic acid mimetics as potent ligands of the myelin‐associated glycoprotein (MAG), a sialic acid binding immunoglobulin‐like lectin (Siglec) that blocks axonal regrowth after injury 80.…”
Section: Carbohydrate‐based Therapeuticsmentioning
confidence: 99%
“…Nevertheless, fucosylated mimics of the Lewis structures are providing promising leads in current clinical trials for the treatment of asthma (Bimosiamose, TBC-1269; Kogan et al, 1998) and sickle cell crisis (GMI-1070; Chang et al, 2010). Recently, Ernst and coworkers used an nuclear magnetic resonance-guided fragment screen to design ligands with a sLe x scaffold attached to a second site ligand (Egger et al, 2013). This approach afforded E-selectin inhibitors with low nM affinities, although these antagonists have yet to be tested in vivo.…”
Section: Engineered Glycans and Glycan Mimics As Therapeutic Agentsmentioning
confidence: 99%